Methods For Forming the Porous Structure of Cellular Concrete - Vladimir Mixaylovich; Djamilya Fazliddinovna Abdullaeva; Marjona Shuxrat qizi Uralova (Research Parks Publishing LLC, 2022)
To create a highly porous structure of cellular concrete, gas formation methods are used; aeration foaming and dry foam mineralization; combined methods.